Analisis Wacana Kritis pada Debat Pilwakot Surakarta Putaran Kedua Tahun 2020 - Indah Wahyuningsih (ESTETIK : Jurnal Bahasa Indonesia, 2021)
This study aims to describe the discourse analysis contained in the second round of the Surakarta pilwakot debate in 2020. In a critical discourse analysis study, the debate can be analyzed using William L. Benoit's functional theory which includes acclaims or claims, attacks or attacks, and defends or defends. This research uses descriptive qualitative research by describing the functional theory contained in the second round of the Surakarta Pilwakot debate. The documentation technique was used to collect data by watching, viewing, and writing the most important points in the second round of the Solo Pilwakot debate live video broadcast. Content analysis techniques were used in this study to obtain the forms of acclaim, attacks, and defends used by candidate pairs in arguing. Based on the results of the analysis, the two pairs of candidates equally made acclaims or claims, recognition as one way to convince their supporters. As for attacks or attacks, candidate pair number 1 is superior in attacking candidate pair number 2. On defends, candidate pair number 1 (Gibran-Teguh) defends based on empirical data or facts as an aspect of knowledge which supports his argument. Another case with candidate pair number 2 (Bagyo-Supardjo) who is not strong enough in doing a defense or defends through answers or responses that are out of the context in question